Iron supplements concomitant with HIF-PHIs in the treatment of CKD anemia - Xue Wang; Cuiting Wei; Delong Zhao; Xuefeng Sun; Fengge Zhu; Yan Mei; Qian Ma; Guangyan Cai; Xiangmei Chen; Ping Li (Karger Publishers, 2023)
Anemia is a common and important complication in patients with chronic kidney disease (CKD). Accordingly, the current treatment is based on erythropoiesis stimulating agents (ESAs) and iron. Hypoxia-inducible factor (HIF) prolyl hydroxylase domain (PHD) inhibitors (HIF-PHIs) have been developed to treat renal anemia through a novel mechanism. HIF-PHIs increase EPO at physiologic blood concentrations and also improve the supply of hematopoietic iron. Iron is the main component of hemoglobin, and ensuring efficient iron metabolism is essential in the treatment of anemia. HIF-PHIs may have advantages in improving iron utilization and mobilization compared to ESAs. Most HIF-PHIs trials revealed a significant decline of hepcidin, increase transferrin level and total iron binding capacity in patients. From a clinical point of view, improvements in iron metabolism should translate into a reduction in the need for iron supplementation, although timely and comparative assessment of iron supplementation across studies are complicated due to the large variability in the iron regimen employed. This review summarizes the mechanism of HIF-PHIs on improved iron metabolism and the route of iron usage in the trials for dialysis-dependent CKD and non-dialysis CKD. And this review also makes an interpretation of the clinical practice guidelines in China and recommendation by Asia Pacific Society of Nephrology.